2016
DOI: 10.1002/tea.21337
|View full text |Cite
|
Sign up to set email alerts
|

Students from non‐dominant linguistic backgrounds making sense of cosmology visualizations

Abstract: This article presents the results of exploratory research with community college students from non-dominant linguistic backgrounds (NDLB) in an introductory astronomy class as they collaborated to reconstruct dynamic cosmology visualizations through drawing. Data included student discourse during the drawing activity, post-activity interviews, and the drawings themselves. This work comes from the theoretical perspective that revealing student competence should be an essential part of science education research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…This difference was unexpected as both dynamic and static visualizations provided identical explanations and there were no explicit prompts asking students to discuss language features. This finding suggests that the use of dynamic visualizations can create learning environments where ELs can use both oral and written forms of “the language of the science classroom” (Lee et al, , p. 221) for various purposes while exploring scientific phenomena (Bracey, ; Brown, ; Rosebery et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference was unexpected as both dynamic and static visualizations provided identical explanations and there were no explicit prompts asking students to discuss language features. This finding suggests that the use of dynamic visualizations can create learning environments where ELs can use both oral and written forms of “the language of the science classroom” (Lee et al, , p. 221) for various purposes while exploring scientific phenomena (Bracey, ; Brown, ; Rosebery et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In another study, Hudicourt‐Barnes () showed that Haitian students with limited English proficiency in grades five through eight were actively engaged in scientific argumentation when using visualization software that presented graphical representations of sound waves. A recent study by Bracey () showed how using cosmology visualizations helped ELs at a community college use scientific language as they worked together to model information from the visualizations.…”
Section: Rationalementioning
confidence: 99%
“…Okebukola, Owolabi, and Okebukola () studied outcomes from science classes taught in students’ home languages (mother tongue) and argued for an increased focus on home language science teaching. In 2017, Buck Bracey () presented evidence for the utility of drawing visualizations as a strategy for allowing students from nondominant language backgrounds to grapple with science, elaborating on the interconnected nature of language use and content acquisition in science. This recent research points to an interplay between diverse linguistic practices, science content acquisition, and identity formation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, constructing representations collaboratively mediates meaning as it enables more knowledgeable others to confront previously held assumptions doi:10.1163/23641177-bja10028 | ASIA-PACIFIC SCIENCE EDUCATION (2021) 1-34 of their peers. For example, Bracey (2017) found that during the constructing of visual representations, English learners drew support from their communicative repertoires as well as each other as they argued. This action facilitated their sense-making of galaxy collisions, which is a complex abstract concept.…”
Section: 1mentioning
confidence: 99%